Gc-ms analysis, phytochemical studies and antimicrobial compounds from bark of Thespesia Populnea (L) Soland EX correa - S. USHA NANDHINI,; R. ROOBINI, (International Journal of Pharma and Bio Sciences, 2017)
The phytochemical analysis and antimicrobial compounds by GC-MS analysis from bark of Thespesia populnea were studied. The confirmation of antimicrobial activity of bark extract was done by agar well diffusion method. Active compounds were extracted by ethanol solvent extraction method. The presence of active compounds were confirmed by UV-Spectrophotometer, FT-IR and GC-MS analysis and it was confirmed that the presence of Methyl salicylate, Hexadecanoic acid- ethyl ether and Oleic acid. The results of this study suggested that the method adopted for extracted active metabolites and can be fruitfully employed for obtaining novel antibiotic compounds to treat various bacterial and fungal diseases.